The use of audio-visual learning media in an effort to increase learning motivation - Rosita Umroh (Institute of Accounting Research and Novation (IARN), 2023)
This media has more capabilities because this media relies on two senses at once, namely the sense of hearing and the sense of sight. With this media it is hoped that it can arouse student motivation in learning and clarify the material presented. This study describes the use of audio-visual learning media in an effort to increase student learning motivation at MTs Surya Buana Malang. With the formulation of the problem that the researcher uses is the use of audio-visual learning media, the role of audio-visual learning media and the supporting and inhibiting factors of audio-visual learning media in an effort to increase student motivation at MTs Surya Buana Malang. This research is a qualitative descriptive research. Data collection was carried out using observation, interview, and documentation methods. Data analysis used descriptive qualitative analysis, namely in the form of written data or from interviews with related parties. The results of this study are as follows: the use of audio-visual media is not broadcast live with a satellite dish but with VCD recordings. The curriculum used is in accordance with the curriculum implemented by the current government, but its implementation is coupled with the use of audio-visual media. And audio-visual media has a role in increasing student motivation. The obstacles encountered in audio-visual learning are a) limited material recording, b) the program cannot be repeated, c) students who are late. And the supports are a) availability of audio-visual media, b) availability of time to use audio-visual media, c) teacher discipline.